Acceptability of beetroot pre-processed under different cooking methods - Ramos, Juliana Arruda [UNESP]; Daiuto, Erica Regina [UNESP]; Fujita, Erika [UNESP]; Carvalho, Lidia Raquel de [UNESP]; Vieites, Rogerio Lopes [UNESP] (Univ Federal Mato Grosso, 2016)
This study aimed to evaluate the acceptability of beet subjected to four heat treatments (steam cooking, cooking in a pressure cooker, cooking in the oven and immersion in water) and three different pre-preparation methods (whole unpeeled, whole and manually peeled, and peeled and sliced in a food processor). The following sensory attributes were analyzed: appearance, odor, texture, flavor and overall evaluation through affective test using a hedonic scale with nine points. Sensory analysis was performed with unselected and untrained tasters of both sexes, aged over 18 years, 60 tasters for each day of analysis. The best sensory acceptance in the oppinion of women was attributed for sliced and steamed beets and the worst for sliced beets cooked in pressure cooker, while for men, the most accepted were whole unpeeled beets cooked in pressure cooker and sliced steamed beets, and the less accepted were sliced beets cooked through immersion in water. For both sexes, the most and less accepted were sliced steamed beets and sliced beets cooked in the oven and whole unpeeled beets cooked in the oven. The biggest losses of color occurred in sliced beets cooked in pressure cooker and immersed in water.
Keywords: Beta vulgaris L.; heat treatment; pre-preparation; sensory analysis